Experimental study of the 3D effects on the performance of RC frame under the loss of an interior column scenario - Widjaja, Ryan William. (2013)
Progressive collapse has always been well-known as one of the main causes of structural damage in close-in detonation conditions. Studies and considerations of how to prevent progressive collapse have been widely examined since the havoc of the Ronal Point in the United Kingdom (UK) in 1968. Consequently, throughout the 1970s, numerous papers concerning over progressive collapse were published. Nevertheless, this topic had been quite unpopular in the 1980s, essentially due to the conditions around the world on that point of time where peace was relatively maintained and there was no significant collapse occurred during that period. It was only after several structural collapse events as a result of terrorist attacks (such as the World Trade Center Twin Towers of New York City collapse in 2001 and the previous attack resulting in the havoc of Alfred P. Murrah Federal Building that was located in Oklahoma City which took place in 1995) that brought back the urgency in the research of structural system that will be able to withstand progressive collapse.